Teachers’ Professional Development in Zambia: Perceptions and Practices - Muyunda, Gift; Yue, Lei; Oranga, Josephine (International Journal of Social Learning (IJSL), 2023)
This study aimed to explore teachers’ perceptions and practices in professional development (PD) activities and the impact of PD on their professional growth. A descriptive mixed-method design was utilized, and the study sample of seven hundred (700) respondents from four primary schools was selected randomly. The results indicate that the program is charming and perfectly designed for the professional development of Zambian teachers; however, there are many flaws in the various steps of the program's implementation, which seem to fail PD activities in teacher training, as the transfer of exercise was found to be very ineffective. The results show that teachers perceived PD as being significant because it improves the teacher's pedagogical knowledge, teaching skills, and updating content knowledge. The results show that the predominant PD practices in schools were workshops, in-service training, and continuing learning. This study argues that PD enhances teachers' pedagogical knowledge, content knowledge, and career growth.